2020
DOI: 10.1080/01446193.2020.1817516
|View full text |Cite
|
Sign up to set email alerts
|

Pandemics, public-private partnerships (PPPs), and force majeure | COVID-19 expectations and implications

Abstract: The novel coronavirus (COVID-19) pandemic is placing unprecedented stress on public-private partnerships (PPPs), creating the real possibility of widespread project failures. The disruption and potential collapse of multiple PPP projects will likely trigger force majeure contractual provisions, but the applicability and efficacy of these generic catch-all clauses remain in question. This critical note therefore discusses the implications of force majeure contractual conditions on PPPs in the COVID-19 epoch. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 27 publications
0
41
0
2
Order By: Relevance
“…These partnerships may have the physical and social infrastructure to immediately improve water access for many vulnerable communities. But the pandemic has created financial stress for PPPs across industries globally and threatens widespread project failure from logistical disruption and new budget constraints, including the loss of revenue from regional lockdowns ( Baxter and Casady, 2020 ; Casady and Baxter, 2020 ). PPP engagement requires caution, as goals and accountability are not always well-aligned between partners, and profit imperatives can clash with equity and other priorities.…”
Section: Discussionmentioning
confidence: 99%
“…These partnerships may have the physical and social infrastructure to immediately improve water access for many vulnerable communities. But the pandemic has created financial stress for PPPs across industries globally and threatens widespread project failure from logistical disruption and new budget constraints, including the loss of revenue from regional lockdowns ( Baxter and Casady, 2020 ; Casady and Baxter, 2020 ). PPP engagement requires caution, as goals and accountability are not always well-aligned between partners, and profit imperatives can clash with equity and other priorities.…”
Section: Discussionmentioning
confidence: 99%
“…Impacts outside of the construction field have been focused on understanding the applicability of the force majeure clause in the current pandemic context (e.g. [ 16 , 25 , 26 ]. [ 26 ], discussed the impact that COVID-19 has had on the Nigerian construction industry [ 26 ].…”
Section: Research Backgroundmentioning
confidence: 99%
“…suggested that given the highly disruptive events COVID-19 has placed on the Nigerian construction industry (e.g., by slowing down completion of projects due to social distancing practices), force majeure contractual clauses should be reviewed among the parties involved so to minimize the challenges that COVID-19 has placed on construction contracts. Similarly [ 16 ], explore the force majeure clause in the context of public-private partnerships (PPP). Casady and Baxter argued that given the important role that infrastructure projects will play in the economic recovery of nations and the stress that COVID-19 is placing on force majeure clauses, it is important that these clauses are reviewed in a comprehensive manner to minimize their impacts on construction projects.…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, it formally defines the protocols that would take over usual operations during times of crisis. There have been considerations that the COVID-19 Outbreak could constitute a Force Majeure event [22]. IT projects are no exceptions and may need such provisions to ensure that businesses can engage in mutually supportive relationships.…”
Section: Covid-19 Impact On It Outsourcingmentioning
confidence: 99%